Catastrophic Forgetting in Language Models - Peng, Tiantian; Tayefeh, Shakila (My University, 2025)
Catastrophic forgetting remains a persistent challenge in the continual learning paradigm of neural networks, particularly in the context of pre-trained language models. This thesis investigates the phenomenon of catastrophic forgetting in large language models (LLMs), with a focus on BERT, through a series of benchmark evaluations. Specifically, we explore the effects of fine-tuning BERT on a vision-andlanguage dataset and subsequently evaluate its performance on GLUE and Super-GLUE tasks to assess the retention of previously learned knowledge. A brute-force approach was employed in an attempt to mitigate forgetting, involving standard finetuning without regularization or memory replay mechanisms. Contrary to expectations, empirical results demonstrate that the fine-tuned models exhibit degraded performance on benchmark tasks compared to the original pre-trained models, highlighting the severity of catastrophic forgetting. These findings emphasize the need for more sophisticated mitigation strategies and contribute to a deeper understanding of transfer learning limitations in current NLP systems.
Keywords: Catastrophic Forgetting; Continual Learning; BERT; Fine-Tuning; Transfer Learning; GLUE; SuperGLUE; Natural Language Processing (NLP)